Modelling and prediction of current harmonics generated by power converters in distribution networks. Issue 15 (18th March 2021) - Moradi, Arash; Yaghoobi, Jalil; Alduraibi, Abdulrahman; Zare, Firuz; Kumar, Dinesh; Sharma, Rahul
Abstract: Predicting current harmonics in distribution networks is essential to find harmonic losses and power quality indices. In order to predict the current harmonics, the effect of grid impedance and voltage distortions on grid‐connected power converters need to be considered. The effects of these parameters on current harmonics can be nonlinear, which complicates the system analysis. Consequently, this paper investigates the impacts of background voltage harmonics, grid impedance, and multi‐parallel grid‐connected converters on current harmonics at a point of common coupling. Moreover, a novel method called combined least squares and kriging (CLSK) is proposed to predict the current harmonics after evaluating the level of system nonlinearity. In the proposed CLSK method, the prediction model is developed by measured voltage and current harmonics at the point of common coupling to identify and predict the current harmonics. This analysis shows that using the proposed CLSK method, the accuracy of the current harmonic prediction is increased compared to the existing methods. The accuracy and the efficiency of the proposed CLSK method are verified by lab experimental results and field measurement data.